Time to stabilization of anterior cruciate ligament-reconstructed versus healthy knees in National Collegiate Athletic Association Division I female athletes - Webster, K. A.; Gribble, P. A. (Journal of Athletic Training, 2010)
Context: Jump landing is a common activity in collegiate activities, such as women's basketball, volleyball, and soccer, and is a common mechanism for anterior cruciate ligament (ACL) injury. It is important to better understand how athletes returning to competition after ACL reconstruction are able to maintain dynamic postural control during a jump landing.